Methodological proposal for the measurement of the incidence of electronic satisfaction and the flow experience in loyalty to the public service company - Baque Romero, Jimmy (2023)
This research focuses on proposing a methodology to measure the incidence of electronic satisfaction and the flow experience on loyalty to the public service company. Three hypotheses are established: the influence of electronic satisfaction on company loyalty, the customer flow experience as an indicator of their loyalty, and electronic satisfaction in terms of bidirectional feedback. Through an exhaustive collection of data and the explanation of its statistical analysis, added to the approach of a survey that answers these questions, it is intended to find results that support the hypotheses. In addition, to demonstrate that the proposed variables have mutual influence. Finally, it seeks to implement this methodology specifically to public sector companies in their information management to improve customer retention and strengthen the relationship with them, highlighting the importance of providing a satisfactory and immersive experience on their digital platforms.